Lúpus eritematoso cutâneo subagudo apresentando-se como eritema anular centrífugo Subacute cutaneous lupus erythematosus (SCLE) manifested clinically as annular erythema centrifugum - Ney Romiti; Sandra Lopes Mattos e Dinato; José Roberto Paes de Almeida; Angela Lapoli; Angelo Sementilli (Sociedade Brasileira de Dermatologia, 2004)
Os autores relatam caso de lúpus eritematoso cutâneo subagudo (LECSA) manifestado clinicamente como eritema anular centrífugo. Ressaltam a diferenciação clínica e laboratorial entre LECSA e lúpus eritematoso sistêmico. Também discutem a conduta terapêutica. The authors describe a case of subacute cutaneous lupus erythematosus (SCLE) manifested clinically as a case of annular erythema centrifugum. The clinical and laboratorial differentiation of SCLE from systemic lupus erythematosus is emphasized, and the best therapeutic conduct is indicated.